(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study was carried out to evaluate the nutrient composition of five selected crops (viz; Bambara nut, Bread fruit, Bush mango, Cocoyam, and sweet potato); and their traditional post-harvest practices. Three different states viz; Rivers, Ebonyi and Akwa-Ibom states were chosen for this study. The crops selected for this study are perceived to be underutilized in the selected study areas, hence, the need to investigate the primary factors mitigating the maximum utilization of these crops. The samples were analysed for proximate composition (moisture, ash, crude fibre, crude fat, crude protein, and carbohydrate) using AOAC standard methods. Data on the traditional post-harvest practices were collected directly from the farmers using structured questionnaire which contained relevant questions based on the objectives of the study. Results of the proximate composition revealed that these crops have rich nutrient composition. However, the overall nutrient composition of these crops varied across the three states. The protein content of bread fruit was 2.50±0.00% in the samples obtained from Rivers state; 14.20±0.00% in the samples obtained from Ebonyi state and 10.25±0.07% in the samples obtained from Akwa-Ibom state. The traditional post-harvest practices associated with these crops differed, with some practices peculiar to the root tubers (cocoyam and sweet potato) while others to the legumes (Breadfruit and Bambara nut) and Bush mango (a fruit). Deductively, poor postharvest handling practices, lack of improved storage facilities restrain the commercialization of these underutilized crops. Hence, the adoption of improved post-harvest technologies would enhance the utilization of these crops.